Comparative Incidence of Crohn’s Disease Among Age Groups and Its Association with ABO and RhD Blood groups - Mariam Elahjal; Muna Elkouha; Rabia Elsalami; Magdi Alhatmi; Ramzi Jummah (AlQalam Journal of Medical and Applied Sciences, 2025)
Crohn’s disease (CD) is a chronic inflammatory disorder that impacts the entire gastrointestinal tract, typically diagnosed in individuals during their second or third decade of life. Recent studies have indicated a correlation between ABO blood groups and susceptibility to various diseases. This study aimed to investigate the distribution of ABO and RhD blood groups among patients with CD, as well as the incidence of CD across different age groups. Additionally, it seeks to highlight the role of heredity in the incidence of CD. Samples from 110 CD patients were represented by 60 males (54.5%) and 50 females (45.5%) who attended gastroenterology outpatient clinics at Tripoli University Hospital (TUH) and Tripoli Central Hospital (TCH) for follow-up. Blood samples were serologically screened for ABO and RhD antigens using tube agglutination tests. The most common blood type was blood group O (50%), followed by blood group A (33.6%). Regarding the RhD factor, 87.3% of study subjects were Rhesus positive. In this study, the most frequently occurring CD cases among age groups were found to be among adults (20 to 39 years), with 64.5%, followed by middle-aged adults (40 to 59 years), which was 22.7%. Furthermore, it was determined that 17.3% and 9.1% of affected individuals possess first-degree and second-degree relatives, respectively. Our results established that the O blood group correlates with a heightened risk of developing celiac disease (CD). The age group most affected was between 20 and 39 years.